Gender, Age, and Teaching Experience Factors in Creative Teaching Practices Among Islamic Education Lecturers - Asep - Kurniawan; Hakan Bayirli (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2024)
This study aims to evaluate creative teaching practices among Islamic Education lecturers at Muhammadiyah University of Cirebon and analyze the differences and relationships between these practices and demographic variables such as gender, age, and teaching experience. This research employs a quantitative approach with a survey method, using a five-point Likert scale questionnaire distributed online to 75 lecturers selected through simple random sampling. The instrument used consists of 24 items with high reliability (α = 0,941). Data analysis was conducted using IBM SPSS Statistics Version 28.0, including normality tests, descriptive analysis, and inferential analysis. The normality test results indicate that the data is normally distributed. Descriptive analysis shows that the lecturers' creative teaching practices are at a high level (mean = 3.99, SD = 0.471), with the item